2003
DOI: 10.1053/jopr.2003.5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of a metal‐ceramic fixed partial denture with a loose retainer

Abstract: In clinical practice, it is necessary to remove a ceramic-veneered fixed partial denture when an abutment becomes loose. When possible, the fixed partial denture is removed in a single piece, allowing recementation when appropriate. A 1-piece removal is challenging, often putting the veneer and abutment teeth at risk for damage. This article describes a technique for fabricating and using a 2-piece matrix that both protects the prosthesis and better directs removal forces along the long axis of the abutments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…Sabit protetik restorasyonların sökümü sırasında uygulanan kuvvetin çevre dokulara ve destek diĢlere zarar vermemesine dikkat edilmesi önemlidir. 27 Bundan dolayı,çalıĢmamızda küçük kuvvetler uygulanarak iĢleme baĢlanmıĢ ve daha sonra kuvvet yavaĢ yavaĢ arttırılmıĢtır. Manuel ve otomatik köprü sökücüler ile çıkarılamayan restorasyonlar kesilerek çıkarılmıĢtır.…”
Section: Tartiġmaunclassified
“…Sabit protetik restorasyonların sökümü sırasında uygulanan kuvvetin çevre dokulara ve destek diĢlere zarar vermemesine dikkat edilmesi önemlidir. 27 Bundan dolayı,çalıĢmamızda küçük kuvvetler uygulanarak iĢleme baĢlanmıĢ ve daha sonra kuvvet yavaĢ yavaĢ arttırılmıĢtır. Manuel ve otomatik köprü sökücüler ile çıkarılamayan restorasyonlar kesilerek çıkarılmıĢtır.…”
Section: Tartiġmaunclassified
“…For removal of loosened retainer of FPD, it requires time for fabrication, and considerably reduction on chair side time. Verrett and Mansueto [37] made use of a two piece matrix on the buccal and lingual surface of the bridge, connected to each other by means of a nut and bolt. Application of tapping force through resin matrix may cause safe removal of the FPD [35].…”
Section: Atd Automatic Fpds Removermentioning
confidence: 99%
“…Retainer failure is a challenging situation especially when luting cements fail under a fixed retainer, whereas another retainer remains cemented. 2 As long ago as 1986, Karlsson 3 reported that 12.6% of patients had undiagnosed loose fixed prostheses retainers and also noted that a loose retainer occurs more frequently if the abutment had been root canal treated.…”
Section: Introductionmentioning
confidence: 99%